Variations of midfacial soft-tissue thickness in subjects aged between 6 and 18 years for the reconstruction of the profile: A study on an Italian sample. (September 2016) - Gibelli, Daniele; Collini, Federica; Porta, Davide; Zago, Matteo; Dolci, Claudia; Cattaneo, Cristina; Sforza, Chiarella
Graphical abstract: Highlights: Facial approximation is based on databases of facial thicknesses. Very few studies were conducted on facial soft thickness of minors. Result show that from 6 to 18 years soft tissues are significantly related with age and sex. A database for soft-tissue thicknesses in children aged between 6 and 18 years was created. Abstract: Facial approximation techniques used in forensic anthropology are based on soft-tissue thickness databases. However most of articles deal with adult populations, and very few studies were conducted on minors. This study aims at providing data concerning facial thickness for George reconstruction, preliminary to the 3D facial approximation. Diagnostic cephalometric X-ray films were obtained from 222 healthy Caucasoid children (91 boys and 131 girls), aged between 6 and 18 years, treated in a Department of Orthodontics of Northern Italy. After setting the Frankfurt plane horizontal, 14 measurements were taken at the mid-facial landmarks: supraglabella, glabella, nasion, nasale, subnasale, superior labial sulcus, labrale superius, stomion, labrale inferius, inferior labial sulcus, suprapogonion, pogonion, gnathion, menton. Mean and standard deviation of soft-tissues thickness at each point were calculated. A two-way analysis of variance (ANOVA) was performed to test the modifications of facial parameters with age and sex (p < 0.01). The results demonstrated that there is an increase in tissue thickness as individuals grow; in most occasions, males showed thicker soft tissues than females of the same age, especially after the adolescent growth spurt. Facial thicknesses at subnasale, superior labial sulcus, labrale superius, labrale inferius, inferior labial sulcus, suprapogonion, pogonion and gnathion significantly modified with age, whereas the same parameters at subnasale, superior labial sulcus, labrale superius, labrale inferius, stomion and suprapogonion were significantly sexually dimorphic. In addition, a database for soft-tissue thicknesses in children aged between 6 and 18 years was created, which may be of interest in cases of facial approximation of Italian minors.